INFLUENCE INVESTMENT OPPORTUNITY SET, OPERATING PROFIT MARGIN, CASH FLOW FROM OPERATING ACTIVITIES AND CASH FLOW TO EQUITY ON POLICY DIVIDEND ON A METAL COMPANY THAT LISTED ON INDONESIA STOCK EXCHANGE - Sri Fitri Wahyuni; Fika Rimalansyah Peride (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2021)
The research objectives in this study are to find out and analyze the effect Investment Opportunity Set, To find out and analyze the effect Operating Profit Margin, To find out and analyze the effect of Cash flow from operating activities, to find out and analyze the effect Cash flow to Equity to the dividend payout ratio, to determine and analyze the effect of the Investment Opportunity Set, Operating Profit Margin, Cash Flow from Operating Activities and Cash Flow to Equity simultaneously on the Dividend Payout Ratio in metal companies listed on the Indonesia Stock Exchange for the 2016-2020 period. This study uses a quantitative approach, the regression analysis technique used in this study is a multiple linear regression analysis technique. The results of this study indicate that there is an influence between the Investment Opportunity Set on Dividend Policy. There is an effect of Operating Profit Margin on Dividend Policy. There is no influence of Cash Flow From Operating Activities on the Dividend Policy in. There is an effect of Cash Flow to Equity on Dividend Policy and the Fcount Value is 12, 130 with a significant level of 0.000, while Ftable is known to be 2.68. Based on these results, it can be seen that Fcount > Ftable (12,130 > 2,68) so that H0 is rejected and Ha is accepted so it can be concluded that the variables of Investment Opportunity Set, Operating Profit Margin, Cash Flow From Operating Activities, Cash Flow to Equity together have significant influence on the Dividend Policy of Metal Companies Listed on the Indonesia Stock Exchange for the 2016-2020 period.